Narrative and identity : an ethical reading of Exodus 4 - Gorospe, Athena E. (Biblical interpretation series, 2007)
Using Ricoeur's theories of narrative and identity, and their ethical implications, this book offers a multi-disciplinary Asian reading of Moses' reverse migration in Exodus 4:18-26, in light of the liminal experience of global economic migration. The work demonstrates the productivity of Ricoeur's threefold movement of prefiguration, configuration, and refiguration for OT studies and contemporary realities. By bringing together the world of an ancient text, a nuanced reading of the text's narrative movement and its history of interpretation, and the bittersweet realities of Filipino overseas workers, this creative study charts the way for an OT hermeneutic that opens up possibilities for the formation of a reader's narrative and ethical identity.